PENGEMBANGAN E-MODUL MATEMATIKA BERBASIS PENDEKATAN KONTEKSTUAL PADA MATERI BENTUK ALJABAR KELAS 7 MTSN 3 KOTA BANJARMASIN - Muhammad Amin Paris; Lia Fauziah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study was motivated by the lack of interest and understanding of students' learning of mathematics, especially in the material of algebraic form. So that the learning process needs to be encouraged by teaching materials that support the learning process. This research aims to find out how the stages of making, the level of validity and the level of practicality of the contextual approach-based mathematics e-module on the material of algebraic form. This research uses the R&D (Research and Development) method with the ADDIE development model. The subjects in this research included 33 seventh grade students, a mathematics teacher and e-module validator. The object of research is the development of a contextual approach-based mathematics e- module on algebraic form material. The results of this research and development have produced a product, namely a contextual approach-based mathematics e-module on algebraic form material. With the e-module development procedure through five stages, namely analysis (Analysis), design (Design), development (Development), implementation (Implementation), and evaluation (Evaluation). The validity level of this e- module has gone through the validation stage by experts, including from material experts getting ‘Valid’ criteria, from media experts getting ‘Valid’ criteria, and from linguists getting ‘Very Valid’ criteria. The level of practicality of e-modules is seen from the results of the educator response questionnaire getting the criteria ‘Very Practical’, and the results of the student response questionnaire getting the criteria ‘Very Practical’